Echoes & eloquences the life and cinema of Gulzar - Chatterjee, Saibal (New Delhi Rupa & Co., 2007)
On the life and cinematic works of Gulazara, b. 1936, Hindi film director, producer, and lyricist.
Keywords: Gulazara -- Criticism and interpretation